Effect of solution treatment on microstructure and properties of Al-Zn-Mg-Cu alloy - WANG Jingtao; SUN Ning; YU Lang; LI Xinghui; MA Fang; WANG Yonghong; CHENG Zhiyuan; GUO Fengjia (Journal of Aeronautical Materials, 2023)
The hot-rolled Al-Zn-Mg-Cu system aluminum alloy was treated with single-stage solution，low temperature-long term & high temperature-short term and low temperature-short term & high temperature-long term，double-stage solution quenching systems. The effects of different solution methods on the structure and properties of Al-Zn-Mg-Cu system aluminum alloy were systematically compared and analyzed by OM，SEM，DSC，EBSD and other technical means，as well as conductivity testing methods. The results show that the selected solution quenching system will not cause the structure to overheat，and can fully dissolve the eutectic second phase of the low melting point in the structure. When 473 ℃/20 min+477 ℃/40 min two-stage solution quenching system is selected，the plate has the best solution effect and the lowest conductivity，which is 27.60%IACS，and the recrystallization degree of the structure is less than 50%. There are {112}〈111〉，{011}〈211〉，{123}〈634〉 deformation texture and {001}〈110〉 shear texture in the structure.